Participation and benefits of SMEs in GVCs in Southeast Asia - López González, Javier (OECD Trade Policy Papers, 2019)
Although global value chain (GVCs) participation in Southeast Asia has been growing, little is known about whether the benefits from participation are accruing to larger firms or if small and medium sized enterprises (SMEs), which make up the majority of companies and employ the bulk of the domestic workforce, are also able to take advantage of the new opportunities on offer. This paper uses detailed firm level data from Southeast Asian countries to split the OECD Trade in Value Added database and map how SMEs have been participating in GVCs. It then identifies the benefits associated with this participation and looks into the policy levers that can help make GVC participation in the region more inclusive. It suggest that policy makers focus on: i) reducing trade costs that hit SMEs hardest; including tariffs, trade agreements and trade facilitation; ii) creating an enabling environment to promote domestic linkages so that SMEs can create partnerships with larger firms and multinationals to export indirectly; and iii) reducing non-tariff measures that are especially onerous for SMEs through wider ASEAN regulatory harmonisation and adopting more flexible rules of origin